2014
DOI: 10.1017/s1368980014002973
|View full text |Cite
|
Sign up to set email alerts
|

Breakfast intake among adults with type 2 diabetes: influence on daily energy intake

Abstract: Objective To assess the association between breakfast energy and total daily energy intake among individuals with type 2 diabetes. Design Cross-sectional study. Daily energy intake was computed from a 24-h dietary recall. Multiple regression models were used to estimate the association between daily energy intake (dependent variable) and quartiles of energy intake at breakfast (independent variable) expressed as either absolute or relative (% of total daily energy intake) terms. Orthogonal polynomial contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Omitting this meal raises concerns, particularly in patients with diabetes. It was shown that individuals consuming breakfast have an improved lipid profile and higher tissue susceptibility to insulin compared to those omitting breakfast [18]. Our study demonstrated that 1.4% of individuals with normal body weight, 2.5% of overweight and 1.6% of obese patients never have breakfast.…”
Section: Discussionmentioning
confidence: 52%
“…Omitting this meal raises concerns, particularly in patients with diabetes. It was shown that individuals consuming breakfast have an improved lipid profile and higher tissue susceptibility to insulin compared to those omitting breakfast [18]. Our study demonstrated that 1.4% of individuals with normal body weight, 2.5% of overweight and 1.6% of obese patients never have breakfast.…”
Section: Discussionmentioning
confidence: 52%
“…Abdominal adiposity, regardless of the presence or absence of nutritional state alterations, is more closely related to cardiometabolic complications in adolescence and to breakfast omission [21]. It is important to emphasize that this last condition can also be associated to the reduction of insulin sensitivity, since the ingestion of this meal has a beneficial effect on appetite regulation and also improves the glycemic response at the next meal, by providing an increase in insulin sensitivity [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Those opting to follow this meal pattern on weekends had on average an unhealthier overall diet characterized by lower intakes of vegetables and fruits, milk and dairy, and higher intake of meat and meat dishes, as well as 3.14-fold higher odds for increased serum ferritin. The most studied meal in the scientific literature is breakfast, which shows that breakfast consist of cereals or toast is associated with satiety, overall daily energy intake, and appetite regulation [ 26 , 27 ], as well CVD risk factors [ 28 ] and atherosclerosis [ 29 ]. The role of other meals, in particular light meal, remained largely unexplored, and requires further research.…”
Section: Discussionmentioning
confidence: 99%